2021
DOI: 10.1080/09297049.2021.1894110
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between two aspects of procedural learning in Tourette syndrome: Enhanced statistical and impaired sequence learning

Abstract: Tourette syndrome (TS) is a childhood-onset neurodevelopmental disorder that primarily affects the cortico-basal ganglia-thalamo-cortical (CBGTC) circuitry and is characterized by motor and vocal tics. Previous studies have found enhancement in procedural memory, which depends on the CBGTC circuitry and plays an important role in the learning and processing of numerous motor, social, and cognitive skills and habits. Based on these studies, procedural hyperfunctioning in TS has been proposed. However, the neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 73 publications
1
32
0
Order By: Relevance
“…In this task, participants receive explicit instructions to pay attention and learn the pattern of the sequential stimuli (dogs appearing in the four possible locations). In contrast, the alternating random elements (penguins in the four possible locations) are learnt incidentally as part of the triplet structures (Nemeth et al, 2013; Tóth‐Fáber et al, 2021). Interestingly, children with GTS (10–15 years of age) showed better learning of triplet probabilities (statistical learning) than TD children.…”
Section: Procedural Memory In Gtsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this task, participants receive explicit instructions to pay attention and learn the pattern of the sequential stimuli (dogs appearing in the four possible locations). In contrast, the alternating random elements (penguins in the four possible locations) are learnt incidentally as part of the triplet structures (Nemeth et al, 2013; Tóth‐Fáber et al, 2021). Interestingly, children with GTS (10–15 years of age) showed better learning of triplet probabilities (statistical learning) than TD children.…”
Section: Procedural Memory In Gtsmentioning
confidence: 99%
“…Therefore, the processing of S‐R connections has been one focus of GTS research (Beste & Münchau, 2018; Goodman et al, 2014; Kleimaker, Kleimaker, et al, 2020; Maia & Conceição, 2017; Shephard et al, 2019). However, the formation of S‐R associations was suggested to be either facilitated (Beste & Münchau, 2018; Delorme et al, 2016; Dye et al, 2016; Kleimaker, Takacs, et al, 2020; Petruo et al, 2019; Shephard et al, 2019; Takács et al, 2018; Tóth‐Fáber et al, 2021; Walenski et al, 2007) or impaired in GTS (Eördegh et al, 2020; Goodman et al, 2014; Kéri et al, 2002; Marsh et al, 2004). To solve this contradiction, a framework is needed that can create a bridge between different fields of GTS research.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that tics and habits have similarities: both are stereotyped actions that are automatically executed and hard to inhibit ( Conceição et al, 2017 ). Several studies have shown enhanced procedural learning, termed procedural hyperfunctioning, in TS ( Dye et al, 2016 ; Takács et al, 2018 ; Shephard et al, 2019 ; Tóth-Fáber et al, 2021b ). An important question emerges: does procedural hyperfunctioning in TS lead to persistent changes?…”
Section: Introductionmentioning
confidence: 99%
“…Several studies focused on procedural learning in TS with most showing intact ( Channon et al, 2003 ; Takács et al, 2017 ) or even enhanced procedural functions ( Walenski et al, 2007 ; Dye et al, 2016 ; Takács et al, 2018 ; Shephard et al, 2019 ; Tóth-Fáber et al, 2021b ). Takács et al (2018) , Shephard et al (2019) , and Tóth-Fáber et al (2021b) all employed variations of a well-known procedural learning task, the serial reaction time task (SRTT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation